Pengaruh Gaya Kepemimpinan Terhadap Disiplin Dokter dalam Ketepatan Waktu Pelayanan Sesuai Standar Pelayanan Minimal (SPM) Rawat Jalan di Rumah Sakit Umum Daerah K.R.M.T Wongsonegoro Tahun 2018 - Roosmalia Isdiani; Sudiro Sudiro (Jurnal Manajemen Kesehatan Indonesia, 2019)
Doctor discipline of on time outpatient service is one of the major complaint from the community as well as hospital management. Doctor presence in outpatient service still have not meet the requirement of minimal standard service which is at 08.00 a.m. Leadership style in hospital management has a great effect on enforcement of doctor discipline on time of outpatient service.Objective of this study is to identify leadership styles applied and which one is the most frequently used by the leader of RSUD K.R.M.T. Wongsonegoro which influenced doctor discipline on time service of outpatient service. This study is a qualitative study. Data collection was conducted using indeepthinterview of 3 (three) specialist doctors assigned as main informan and 3 (three) triangulated respondents, namely: hospital director, chief of medical services and head of outpatient sevices. Result of this study shows there are several leadership style applied: auotocratic, democratic, transactional and tranformasional. The most frequently used leadership style which influenced doctor discipline in time of outpatient service are: 1. Ttransformational in which the leader encourage, inspire and appreciate doctor, so the doctors implement policy from the hospital leader because they were appreciated, 2. Transactional in the form of reward and punishment so the doctors implement policy because they were expect reward if they carry out the task well.